ANALISIS EFISIENSI SISTEM TATA NIAGA GULA DI INDONESIA - Ninuk Rahayu Ningrum; Ernawati Munadi; Tjahya Widayanti (Buletin Ilmiah Litbang Perdagangan, 2007)
Debate on Indonesia’s sugar polisy was stimulated by the sharp increase in the sugar retail price after the implementation of import regulatory policy regim based on the Trade and Industrial Ministry Decree No. 643/MPP/Kep/9/2002.23 September 2002 revised with the Trade and Industrial Ministry Decree No. 527/MPP/Kep/9/2004/and followed by Ministry of Trade Decree No. 19/M-DAG/PER/4/2006 tanggal 19 April 2006.UsIng the annual data for the period of 1998-2004,this study examines the “reasonable sugar retail price “in Indonesia using two approaches i.e (1) import parity and (2) production cost and distribution ; and based on those reasonable sugar retail prices, this study try to analize the  efficiency of the “system tataniaga gula “in Indonesia.The results show that because of the government policy intervension, sugar retail price paid by the sugar cosumer in Indonesia is higher than if no government intervention ( free Trade). It is about 43.07 % and 3.43.% higher based on the first and second approach, respectively, moreover , due to the various, government policies related to tariff and import regulation, cosumer lost for about Rp. 3.8 – Rp 6.2 Trillion a year, but producer get benefit for about Rp.3.2 – Rp 5.2 Trilion ayear. Hence, The dead weight loss due to the”system tataniaga gula “is about Rp. 06- 10 trillion a year.